Serum gamma-glutamyl transferase level as a risk factor in acute stroke - Quazi M. Ismail; Manoj K. Prasad; Sujeet Marandi; Rishi T. Guria; Ajit Dungdung (Journal of Family Medicine and Primary Care, 2023)
Background: Worldwide stroke is the second major cause of mortality and the fourth prominent cause of disease load after coronary heart disease and all types of malignancy. Greater than 3/4th of these cases are in low-priced and middle-priced nations. Several epidemiological studies have shown that alcohol consumption is a risk factor for stroke. The correlation between alcohol consumption and stroke involves various processes. For excessive alcohol consumption, GGT (gamma glutamyl transferase) is used as a marker. The study aims to see whether serum GGT level is an independent risk factor for stroke in young and elderly patients who do not have a history of alcohol intake. Material and Method: The study is an analytical cross-sectional comparative hospital-based study done in the Department of Medicine, RIMS, Ranchi from November 2019 to April 2021. A total number of 100 cases including both sexes who presented with the first episode of stroke have been compared with 100 age–sex-matched healthy control subjects without any cerebrovascular or cardiovascular disease meeting inclusion and exclusion criteria. Analysis of data is done by SPSS software and R studio software. Result: Serum GGT is lower in the age group of 40–60 years (24-hour GGT mean 50.70 U/L+SD 16.86) than the age group of 60–80 years (24-hour GGT 65.89 U/L+SD59.04) with a P value of 0.005. This is also true in 48-hour GGT (48.02 U/L+SD16.02) in 40–60 years compared to 57.94 U/L+SD42.81 in 60–80 years with a P value of 0.001 and 72-hour GGT (44.80 U/L+SD16.98) in 40–60 years compared to the mean (56.16 U/L+SD43.82) in 60–80 years with a P value of 0.001. This suggests that serum GGT level is significantly lower in the 40–60 years age group with a P value < 0.01. The serum GGT level in the case population is mean 58.30 (U/L) + SD43.87, and that in the control group is mean 17.48 (U/L) + SD4.32 with P value < 0.001. This implies an increased level of serum GGT level in stroke patients. Conclusion: Serum GGT level is independently correlated with stroke even in the presence of other risk factors for stroke such as diabetes mellitus, hypertension, and dyslipidemia. Serum GGT level is more in hypertensive, dyslipidemic, and ischemic stroke patients than in non-hypertensive, non-dyslipidemic, non-ischemic stroke patients, but serum GGT level cannot predict the outcome (survival or death) in stroke patients.